Fermentation properties and functional stability of dough starter Jiaozi and Laomian after frozen storage - Li, Haifeng; Lv, Yulan; Zhang, Yingmiao; Wang, Xifeng; Yang, Xiaohong; Qu, Jianhang (Frontiers in Microbiology, 2024)
Purpose: This study aims to investigate the effects of frozen storage on the stability of traditional dough starters of China. Methods: The microbial community structure and abundance of related metabolic genes in the different fermented sourdoughs made by starters of Jiaozi (JZ) and Laomian (LM) before and after frozen at -20 °C for half a year were analyzed using the Shotgun metagenomic sequencing method, and differences in texture characteristics among the steamed bread were also compared by formal methods. Results: The fermentation ability (FA) and metabolic activities of yeast in the JZH sourdough (started by JZ which stored at -20 °C for half a year) were better than that of LMH sourdough (started by LM which stored at -20 °C for half a year). The dominant genera of Acetobacter increased in JZH0 sourdough (started by JZH and fermented for 0 h) and decreased for Lactobacillus. Lactobacillus (98.72%), Pediococcus (0.37%), Saccharomyces (0.27%), and Acetobacter (0.01%), were dominant in sourdough LMH0 (started by LMH and fermented for 0 h). The gene abundances of “oxidative phosphorylation-related enzymes” and the “biosynthesis of glutamate”-related enzymes, genes about “biosynthesis of glutamate”, and “unsaturated fatty acid” were more in JZH0 than that of the JZ0 sourdough (started by JZ without frozen and fermented for 0 h). The good FA of the yeast, acid production capacity of bacteria in the sourdough, and quality of the JZH steamed bread (made by JZH starter) indicating the better-freezing tolerance of the microorganisms in JZ than that of the LM. Conclusion: Suggesting the better application potential of the JZ as fermentation starter in actual production.